The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsnano.3c05387
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Energy Transfer Driven by Electrochemical Tuning of Methylene Blue on Single Gold Nanorods

Hyuncheol Oh,
Emily K. Searles,
Subhojyoti Chatterjee
et al.

Abstract: Plasmonic photocatalysis has attracted interest for its potential to generate energy-efficient reactions, but ultrafast internal conversion limits efficient plasmon-based chemistry. Resonance energy transfer (RET) to surface adsorbates offers a way to outcompete internal conversion pathways and also eliminate the need for sacrificial counter-reactions. Herein, we demonstrate RET between methylene blue (MB) and gold nanorods (AuNRs) using in situ single-particle spectroelectrochemistry. During electrochemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Lu and Lew conclude that SMEC will allow indirect detection of nonfluorescent electroactive species, with future goals of studying local concentrations, redox states, and electron-transfer kinetics using SMEC. In another example, Oh et al demonstrate the ability to efficiently and controllably induce resonance energy transfer between Au NRs and their surface adsorbate, methylene blue molecules . The redox state of methylene blue can be electrochemically modulated between the oxidized state, which exhibits significant spectral overlap with Au NRs, and the reduced state, which exhibits little to no spectral overlap with Au NRs.…”
Section: Single-entity Opto-electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Lu and Lew conclude that SMEC will allow indirect detection of nonfluorescent electroactive species, with future goals of studying local concentrations, redox states, and electron-transfer kinetics using SMEC. In another example, Oh et al demonstrate the ability to efficiently and controllably induce resonance energy transfer between Au NRs and their surface adsorbate, methylene blue molecules . The redox state of methylene blue can be electrochemically modulated between the oxidized state, which exhibits significant spectral overlap with Au NRs, and the reduced state, which exhibits little to no spectral overlap with Au NRs.…”
Section: Single-entity Opto-electrochemistrymentioning
confidence: 99%
“…In another example, Oh et al demonstrate the ability to efficiently and controllably induce resonance energy transfer between Au NRs and their surface adsorbate, methylene blue molecules. 229 The redox state of methylene blue can be electrochemically modulated between the oxidized state, which exhibits significant spectral overlap with Au NRs, and the reduced state, which exhibits little to no spectral overlap with Au NRs. The extent of resonance energy transfer can be found by monitoring changes in the line width of the Au NR’s dark-field scattering spectrum as a function of applied potential, ultimately reporting on SE plasmon damping dynamics while also allowing methylene blue redox chemistry to be indirectly monitored.…”
Section: Single-entity Opto-electrochemistrymentioning
confidence: 99%
“…The findings give guidance for designing plasmonic metal–molecular photocatalysts. The key for achieving hot-carrier transfer in these metal–molecular systems lies in the hybridization of molecular orbitals and spectral overlap between the plasmonic donor and the molecular acceptor. , …”
Section: Reveal Spr Mechanism At Single-particle Levelmentioning
confidence: 99%
“…Recently, Oh et al investigated plasmon damping dynamics in plasmon-enhanced electrocatalytic reactions. The authors obtained line width (Γ), resonance energy (Eres), and intensity (I) from individual Au NRs during electrochemical redox reactions . They observed that the homogeneous line width was broadened when the E res of the Au NRs overlapped with the π → π* transition dipole energy of methylene blue.…”
Section: Reveal Spr Mechanism At Single-particle Levelmentioning
confidence: 99%
“…28 A comprehensive understanding of the mechanisms governing the creation and distribution of HCs is crucial for advancing our knowledge of LSPR-facilitated photocatalysis. 29–42…”
Section: Introductionmentioning
confidence: 99%